In vitro circumvention of cisplatin resistance by the novel sterically hindered platinum complex AMD473 - Holford, J; Sharp, SY; Murrer, BA; Abrams, M; Kelland, LR (British journal of cancer, 1998)
A novel sterically hindered platinum complex, AMD473 [cis-aminedichloro(2-methylpyridine) platinum (II)], has been selected for phase I clinical trials due to commence in 1997. AMD473 was rationally designed to react preferentially with nucleic acids over sulphur ligands such as glutathione. This report documents the in vitro circumvention of acquired cisplatin resistance mechanisms in human ovarian carcinoma (HOC) cell lines by AMD473. In a panel of 11 HOC cell lines, AMD473 showed intermediate growth inhibition potency (mean IC50 of 8.1 microM) in comparison to cisplatin (mean IC50 of 2.6 microM) and carboplatin (mean IC50 of 20.3 microM). AMD473 showed only a 30.7-fold increase in IC50 value from the most sensitive to the most resistant HOC cell line, whereas for cisplatin it was 117.9-fold and for carboplatin 119.7-fold. AMD473 also showed significantly (P < 0.05) reduced cross-resistance to cisplatin in a panel of three cell lines with known acquired platinum drug resistance mechanisms (mean RF for AMD473 was 1.9, for cisplatin 9.1). Cellular accumulation of AMD473 was not reduced in two HOC cell lines (A2780cisR and 41McisR), in which reduced cisplatin accumulation is a major mechanism of acquired cisplatin resistance. AMD473 naked-DNA binding was significantly less affected (P < 0.05) than that of cisplatin by the presence of 5 mM glutathione. Also, AMD473 almost completely circumvented acquired cisplatin resistance in a cell line (A2780cisR) with fivefold elevated intracellular glutathione levels compared with the parent A2780 cell line when measured by clonogenic assay (RF 4.5 for AMD473 vs RF 18 for cisplatin). AMD473 also showed a lower increase in IC50 than cisplatin in an A2780 cell line model with artificially elevated glutathione levels. AMD473 DNA binding was slower than that of cisplatin on both naked and cellular DNA. AMD473 also formed DNA interstrand cross-links (ICLs) at a slower rate than cisplatin (peak ICL formation was at 5 h for cisplatin vs > or = 14 h for AMD473) after equitoxic doses were exposed to HOC cells for 2 h. AMD473 ICLs in the CH1 HOC cell line were slowly formed and showed no visible signs of being repaired 24 h after removal of drug. This was paralleled by a slower, longer lasting induction of p53 protein by equitoxic doses of AMD473 in HOC cell lines with wild-type p53. This new class of sterically hindered platinum compound, selected for clinical trial in 1997, may therefore elicit improved clinical response in intrinsically and acquired cisplatin-resistant tumours in the clinic.